Abelian covers of alternating groups - Barrantes, Daniel (2016)
Let G = A n , a finite alternating group. We study the commuting graph of G and establish, for all possible values of n barring 13, 14, 17, and 19 whether or not the independence number is equal to the clique-covering number.